Development of Interactive Multimedia Based on Problem-Based Learning in the material on the Form of Substances and Their Changes to Improve Science learning Outcomes - Shindy Auliya; Aldina Eka Andriani (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
The utilization of technology-based learning media by teachers has not been done optimally, resulting in low student learning outcomes, which is reflected in 64% of students who do not meet the Learning Objectives Achievement Criteria (KKTP). This study aims to describe the development design and to test the feasibility and effectiveness of an interactive multimedia program based on Problem-Based Learning to improve the learning outcomes of fourth-grade students at SDN Ngaliyan 03, Semarang City. This type of research is Research and Development (R&D) with the ADDIE development model. Twenty-eight fourth-graders from SDN Ngaliyan 03 in Semarang City served as the research subjects. Both tests (pretest and posttest) and non-test methods (observation, interviews, questionnaires, and documentation) were used to collect data. N-Gain, t-tests, and normality tests were used in data analysis. The results of the study showed that an interactive multimedia module on changes in the state of matter, developed using Problem-Based Learning syntax, was accompanied by the use of the PhET Colorado virtual laboratory as a learning stimulus through virtual experiments. Expert validation showed a feasibility level of 91.66% from material experts and 93.75% from media experts, with a very feasible category, reinforced by teacher responses of 92% and student responses of 95% which were also in the very feasible category. The effectiveness of the media is shown by an increase in pretest and posttest scores of 38.40, a t-test result of 0.000, and an N-Gain value of 0.6720, meeting moderate criteria. Based on this research, it can be concluded that an interactive multimedia Problem-Based Learning module on states of matter and their changes has been successfully developed, is highly feasible, and is effective in improving fourth-grade students' science learning outcomes at SDN Ngaliyan 03, Semarang City.